If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 2 = 4(x + -7) Reorder the terms: 2 + y = 4(x + -7) Reorder the terms: 2 + y = 4(-7 + x) 2 + y = (-7 * 4 + x * 4) 2 + y = (-28 + 4x) Solving 2 + y = -28 + 4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + y = -28 + -2 + 4x Combine like terms: 2 + -2 = 0 0 + y = -28 + -2 + 4x y = -28 + -2 + 4x Combine like terms: -28 + -2 = -30 y = -30 + 4x Simplifying y = -30 + 4x
| x+0.5x+x=20 | | 6(x-1.1)=9.3 | | 8s+3=54 | | 43-5x=13-8x | | x^3-35*x^2+27*x-280=0 | | x+3*2=10 | | x+2.2=8.5 | | 1-x-7x=-87 | | 8b^2+6b+1= | | 2a+4=2b-3 | | -2a+3a= | | 3=6+3u | | 8x^2=20y | | X^0=13 | | z-8=5z+3 | | (29.5-.5x)/4=(22.5-.5x)/3 | | 20-11x=20x+1 | | 21c+15-c=15 | | -9u-27=3(-3u-9) | | 4x+8=-34+-3x | | 4c+8=-34-3x | | (8p-3)(6p+7)= | | 3x+5-2x+1= | | 3(a-4)-2(5-a)= | | 3(3x-4)=8x-4-2x | | B^2-14d-45=0 | | 2x-3=3-x | | 3x*56b+-16=1 | | 3y-15=5 | | x-x^2=12(x+2) | | 3m(2m-7)=0 | | 2y(-y+6)= |